Da'wah Value Based on Local Wisdom in the Paliare Ceremony Tradition in Lampung Province - Muhamad Bisri Mustofa; Yunita Sari; Siti Wuryan (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2024)
This article discusses the value of da'wah based on local wisdom in the tradition of the paliare ceremony in Lampung province, considering that the community has local wisdom values and has a reciprocal relationship. The diversity of society that influences cultural diversity in the form of Semende community rituals based on local wisdom is closely related to community life, community relations, and life search systems, safety and happiness. One of the elements of culture and belief that is still preserved in the people of Lampung province is a traditional ceremony carried out in the form of a sacred event showing local wisdom in the tradition of the Pangku Paliare ceremony which is held every year on 25 Muharram. The formulation in this study is how the tradition of the Pangku Paliare ceremony and how the values of da'wah in the Pangku Paliare Ceremony Tradition. This type of research is qualitative research using the methods of observation, interview, documentation. This study succeeded in describing the value of da'wah appearing in local wisdom in the pangku paliare upacra tradition, namely in the value of silahtuhrahmi, worship, and helping.